O sistema permanente de avaliação da educação básica do Ceará - SPAECE – e a prática docente no contexto de crise estrutural do capital - Silva, Daniele Oliveira (2019)
The aggravation of the structural crisis of capital, a thesis defended by István Mészáros (2002), presents us with several reverberations such as the intensified class struggle and the bourgeois ideological decay in the production of knowledge (Lukács, 2013). In this context, we have the current concern of addressing the evaluation proposal of the SPAECE-Permanent Evaluation System of Basic Education of Ceará- implemented in 1992 by the Ceará State Government, which seeks to understand how this evaluation interferes with the teacher training. This study is based on the Marxian perspective, whose method of investigation is based on dialectical historical materialism, an approach to understanding reality based on the historicity, dialectic and contradiction of the object, and its multiple subjective and objective relations in the real. Finally, we believe that the present research contributes to the reflection about the inversion that is taking place in the Brazilian educational system, which, to characterize a quality school, takes as its core the result of the evaluation made through the training exercise with students throughout the period. school year, rather than worrying about the democratization of the knowledge produced by mankind.